Executive Functions and High Intellectual Capacity in School-Age : Completely Overlap? (2018)
ABSTRACT: Objective: To analyze the relationship between the dimensions of the executive function and intellectual capacity in children with high academic performance. Method: an analytical, observational, prospective study with a non-random sample of 104 children between 7 and 11 years of age, belonging to educational institutions in Medellín, Colombia, divided into groups according to the measure of Total Intellectual Capacity (TIC): 1. Those with an average TIC of between 85-115. 2. Children with higher IC or those with scores ranging from 116-129 and 3. Children with TIC of ≥ 130, known as exceptional talents. They are provided executive function tests that are in compliance with bioethical conditions. Results and conclusions: The Intellectual Capacity is not a concept analogous or synonymous to executive function. This study demonstrates that the common element among all participants is high academic performance and an absence of alteration of the executive function. Finally, an adequate executive functioning makes high academic performance possible